Dilemmas of educational management in times of exception: Challenges for the initial level (Praxis Educativa, 2024)
This article presents voices of those who participated in one of the conversations framed in the II Cycle of Conferences Webinars and Education: “Dilemmas of educational management and current emergencies”, held in 2021 (UNQui- UNICEN).It is assumed that the cycle was an opportunity to analyze, in the context of the pandemic, the experiences lived from the stories of researchers and managers. The resonances allow identifying coordinates that can be taken by management, representing a possibility to review positions in the post-pandemic. The focus of the meeting was “Dilemmas of educational management at the initial level and current emerging ones”, around which the perspectives of two provincial education managers and a researcher in the field converged. Updating views on the experiences in the territory allows us to raise the challenges that arise for the management of education in current times and propose new perspectives for the management of our educational systems.
Keywords: Management, education, childhood, pandemic, experience